Design and Test of an Energy-Saving Bionic-Inspired Rotary Blade: A Study on Power Consumption and Soil Surface Quality - Yue Qin; Yunpeng Gao; Chenggong Xie; Jiarui Tong; Qi Wang; Xin Feng (Agriculture)
To reduce the power consumption of rotary tillage and enhance the operational quality of rotary tillage, a rotary blade that imitates the surface of a pufferfish was designed through reverse engineering. The bump structure on the pufferfish surface was employed to decrease the power consumption when the blades till the soil. The performance of the bionic blade was investigated. A single-factor soil bin test was conducted, with the forward speed of the rotary tiller and the rotation speed of the blade shaft serving as the test factors, and the power consumption of the rotary tiller and the ground surface flatness as the evaluation indexes. The test results revealed that the power consumption of the rotary tiller initially decreases, then increases, and finally decreases with the increase in the forward speed of the rotary tiller. It is positively correlated with the rotation speed of the blade shaft. The ground surface flatness is positively correlated with the forward speed of the rotary tiller but negatively correlated with the rotation speed of the blade shaft. Compared with the rotary tiller with standard IT225 blades, the rotary tiller with bionic blades achieves a 9.4% reduction in power consumption and a 6.5% improvement in ground surface flatness. This study has demonstrated that the bump structure of the pufferfish surface can effectively reduce the power consumption of the blades and enhance ground surface quality, thus offering novel insights for the development of energy-saving tillage tools.